Report on the identification of nutritional quality in the population of promising apomictic hybrids - Hernández, Luis Miguel; Mazabel, Johanna; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2020)
A group of 131 selected hybrids were evaluated for nutritional quality traits during 2020. Acid detergent fiber ranged from 27.8 to 37.0% with an average of 32.9%; Digestibility ranged from 41.5 to 55.4% with an average of 47.7%; Dry mater values ranged from 21.8 to 35.1% with an average of 28%; Neutral detergent fiber ranged from 62.4 to 73.9% with an average of 68.2%; and Crude protein ranged from 4.6 to 11.3% with an average of 7.5%. For all the evaluated traits, some hybrids performed better than the commercial benchmark.